2011
DOI: 10.1088/0031-9155/56/23/019
|View full text |Cite
|
Sign up to set email alerts
|

Computational modeling of temperature elevation and thermoregulatory response in the brains of anesthetized rats locally exposed at 1.5 GHz

Abstract: The dominant effect of human exposures to microwaves is caused by temperature elevation ('thermal effect'). In the safety guidelines/standards, the specific absorption rate averaged over a specific volume is used as a metric for human protection from localized exposure. Further investigation on the use of this metric is required, especially in terms of thermophysiology. The World Health Organization (2006 RF research agenda) has given high priority to research into the extent and consequences of microwave-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 44 publications
1
35
0
Order By: Relevance
“…The computational rat model (8-week-old rat) was developed from computed tomography (CT) images [7]. The rat model was composed of the following six tissues: muscle, skin, fat, eye, bone, and brain.…”
Section: Models and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The computational rat model (8-week-old rat) was developed from computed tomography (CT) images [7]. The rat model was composed of the following six tissues: muscle, skin, fat, eye, bone, and brain.…”
Section: Models and Methodsmentioning
confidence: 99%
“…The blood perfusion in the brain was given as follows, based on our rat measurements for local RF exposure [7]:B(boldnormalr,t)=B0(r)(1+FHSΔTH(t))·2ΔT(r)/FBB, where F HB (=0.053 °C −1 ) and F BB (=13.9 °C) denote weighting coefficients in relation to the variations in the core and brain temperature elevations, respectively [25]. …”
Section: Models and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following this study, animal SAR values were calculated and reported for mouse, rat, rabbit, and pig under RF exposures of 800 MHz-2 GHz cellular phone electromagnetic fields. 22,36,44,54,[113][114][115][116][117][118][119][120][121][122][123] Dosimetry calculations were performed for the exposure of mice and rabbit to 2.45 GHz WiFi frequencies. [124][125][126][127][128][129] Fig.…”
Section: B Nonionizing Radiation Dosimetrymentioning
confidence: 99%